Discharge data series of Begura de Salma River (Mallorca, Spain): January 2015-October 2018 - Joan Estrany; Maurici Ruiz-Pérez; Raphael Mutzner; Josep Fortesa; Beatriz Nácher-Rodríguez; Miquel Tomàs-Burguera; Julián García-Comendador; Xavier Peña; Adolfo Calvo-Cases; Francisco J Vallés-Morán (PANGAEA, 2020)
Here we provide the data set obtained as described in detail in Estrany et al. (2020, doi:10.5194/nhess-2019-304); a brief description is presented below. A hydrometric gauging station is located where the Begura de Salma River enters Sant Llorenç des Cardassar, a village located in the northeastern part of Mallorca island (Spain). The station was built by the water authority in the 1970s. After years of abandonment, in 2015 the MEDhyCON Research Group installed within the gauge house a Hobo Water Level U20L-04, which measures the water stage by 1-minute readings, accumulating 15-minute average values. The station is located at the very beginning of the concrete channel that takes the river through the village. Closing a drainage basin of 23 km2, it is located ca. 50 m upstream from the first of the five bridges that cross the river within the village. In the absence of direct flow measurements for Q estimation, a complete two-dimensional hydraulic model was applied with HEC-RAS 5.0.6 software (November 2018 version) in order to establish a stage-discharge rating curve. The hydrological monitoring period was from 10th January 2015 to 31st October 2018, including the catastrophic flash-flood event occurred the 9th October 2018. This gives a series of almost 4 hydrological years.